CMIP6 Models Trend Toward Less Persistent European Blocking Regimes in a Warming Climate - Dorrington, Josh; Strommen, Kristian; Fabiano, Federico; Molteni, Franco (John Wiley and Sons, 2023)
The response of the Euro-Atlantic wintertime circulation to climate change is deeply uncertain. The Atlantic jet is caught in a “tug-of-war” between rapid warming trends in both the tropics and the Arctic leading to debate over the changing “waviness” of the jet, which is subject to strong non-linearity and internal variability. From the complementary perspective of weather regimes, there is considerable uncertainty in how atmospheric blocking will alter under climate change. By applying the hybrid approach of geopotential-jet regimes to 6th phase of the coupled model inter-comparison project projections, we show that the centers of action of anticyclonic regimes hardly alter even under severe warming. Instead, regimes are expected to become less persistent, with zonal flow conditions becoming more prevalent, although models disagree on the details of regime changes. Finally, we show the regime response can be captured qualitatively in a simple Lorenz-like model, emphasizing the conceptual link between observed regimes and those in basic mathematical systems.